Analisis Pemberian Kredit pada Koperasi Simpan Pinjam Pengembangan Pedesaan (KSP3) Nias di Kota Gunungsitoli - Selfilia Annastasia Benaria Telaumbanua; Hendra Nazmi (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
This study aims to obtain accurate information related to: (1) Procedures for granting credit to members at KSP3 Nias in Gunungsitoli City in the period 2020-2021, (2) Obstacles faced in granting and returning credit to members at KSP3 Nias in Gunungsitoli City in for the period 2020-2021, (3) The solution made by the management for the obstacles to returning credit to members at KSP3 Nias in Gunungsitoli City in the period 2020-2021. The method used in this study is a qualitative descriptive method, with the data source in the form of primary data. The results of this study indicate that the procedures, obstacles, and solutions faced in credit at KSP3 Nias are very easy. Both from application and credit return